Drinking Water Treatment Residuals to Control Phosphorus in Soils - Sampson Agyin-Birikorang; George A. O'Connor; Thomas A. Obreza (EDIS)
SL-300, a 7-page illustrated fact sheet by Sampson Agyin-Birikorang, George A. O’Connor, and Thomas A. Obreza, describes the phosphorous problem in Florida, and the use of this byproduct of municipal drinking water purification as a soil amendment to reduce nonpoint source pollution by phosphorous. Includes further readings. Published by the UF Department of Soil and Water Sciences, July 2009.